The manifestations of alienation in the poetry of the contemporary Iraqi poet" Majid Al-Rabie " - Al-Shammari, Ali Mahmoud Habib (Al-Adab Journal, 2021)
The research deals with the study of the phenomenon of alienation and its various types in the poetry of Majid al-Rabei, the contemporary Iraqi poet. The feeling of alienation arose in him for various reasons. In preparing this research, the researcher relied on the descriptive and analytical approach to find the different types of alienations, relying on modern literary sources, especially the poetry collection of the poet Majid al-Rubaie. Religious, Brotherhood, political and other alienations, as a result of the woes and crises suffered by Iraqi society, including the deterioration of Iraq in wars and occupation and other matters that have caused destruction to Iraq. About these meanings. The reason for choosing this poet to study is that the poet does not know him as students and researchers as he deserves, when studying his poetry during examination of the sections of alienation in his life. As well as knowing the poet’s reaction to this alienation and other matters in his poetry.